zapisz w postaci sumy algebraicznej



Zapisz W Postaci Sumy Algebraicznej class=

Odpowiedź :

Hej!

a]

[tex](x+1)^3=x^3+3\cdot x^2\cdot1+3\cdot x\cdot1^2+1=\\\\=\huge\boxed{x^3+3x^2+3x+1}[/tex]

b]

[tex](x-1)^3=x^3-3\cdot x^2\cdot1+3\cdot x\cdot 1^2-1^3=\\\\=\huge\boxed{x^3-3x^2+3x-1}[/tex]

c]

[tex](x+3)^3=x^3+3\cdot x^2\cdot3+3\cdot x\cdot3^2+3^3=\\\\=\huge\boxed{x^3+9x^2+27x+27}[/tex]

d]

[tex](x-4)^3=x^3-3\cdot x^2\cdot4+3\cdot x\cdot4^2-4^3=\\\\=\huge\boxed{x^3-12x^2+48x-64}[/tex]

g)

[tex](3x+1)^3=(3x)^3+3\cdot(3x)^2+3\cdot3x\cdot1^2+1^3=\\\\=27x^3+3\cdot9x^2+9x\cdot1+1=\\\\=\huge\boxed{27x^3+27x^2+9x+1}[/tex]

Użyte wzory :

[tex](a-b)^3=a^3-3a^2b+3ab^2-b^3\\\\(a+b)^3=a^3+3a^2b+3ab^2+b^3[/tex]